EFFECT OF PSYCHOEDUCATION ON ANXIETY IN PATIENTS WITH CORONARY HEART DISEASE - Yuli Sulistiyo; Bedjo Santoso; Shobirun Shobirun; Soeharyo Hadisaputro; Leni Latifah; Rr Sri Endang Pujiastuti (Belitung Nursing Journal, 2017)
Background: Cardiovascular heart disease still remains high in Indonesia. Various interventions have been implemented as an effort to deal with cardiovascular disease. However, little is known about intervention to reduce anxiety in patients with cardiovascular disease although anxiety is related to angina attack in this patient. Psychoeducation is considered effective in decreasing anxiety. Objective: To examine the effect of psychoeducation in decreasing anxiety in patients with coronary heart disease (CHD) at the General Hospital of Semarang, Indonesia Methods: This was a quasi-experimental design with pretest posttest control group design. The study was conducted in the inpatient wards of the General Hospital of Semarang on 17 January until 8 March 2017. Fifty-six respondents were recruited using consecutive sampling, with 28 assigned in the experiment and control group. Hamilton Anxiety Rating Scale (HARS) was used to measure anxiety levels. Paired t-test and Independent t-test were used for data analysis. Results: Paired test showed that there was a statistically significant effect of psychoeducation on anxiety level in the experiment group with p-value 0.001 (<0.05), and significant effect of given a brochure of CHD on the anxiety level in the control group with p-value 0.001 (<0.05). Independent t-test showed a statistically significant difference of anxiety level after intervention in the experiment and control group with p-value 0.001 (<0.05). The mean anxiety level in the experiment group (22.46) was lower than the mean anxiety level in the control group (41.54). Conclusion: Psychoeducation is effective in reducing anxiety levels in patients with CHD. It is suggested that psychoeducation can be used as one of nursing intervention in an effort to reduce anxiety in patients with CHD.